2011
DOI: 10.1111/j.1532-950x.2011.00909.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Durotomy on Laser‐Doppler Measurement of Spinal Cord Blood Flow in Chondrodystrophic Dogs with Thoracolumbar Disk Extrusion

Abstract: Durotomy does not increase SCBF in dogs with disk extrusion associated spinal cord compression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 20 publications
0
20
2
2
Order By: Relevance
“…Consequently one can assume that a durotomy, during which CSF leakage occurs, may have effects similar to direct CSF drainage and may also reduce ITP. It has been suggested that durotomy relieves, to some degree, intramedullary compression in chondrodystrophic dogs with naturally occurring disk extrusion, but its real therapeutic value is still debated . In our study, ITP in dogs with disk extrusion was significantly elevated compared with ITP in healthy dogs (control group); however, ITP of dogs with disk extrusion (group 1) were less than those reported in the experimental study by Kazama et al Based on the observation that SCBF only seems to be influenced where ITP is markedly increased (up to 20/40 mmHg), it may be hypothesized that the effect of a CSF drainage (durotomy) on SCBF may depend on the magnitude of ITP increase.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Consequently one can assume that a durotomy, during which CSF leakage occurs, may have effects similar to direct CSF drainage and may also reduce ITP. It has been suggested that durotomy relieves, to some degree, intramedullary compression in chondrodystrophic dogs with naturally occurring disk extrusion, but its real therapeutic value is still debated . In our study, ITP in dogs with disk extrusion was significantly elevated compared with ITP in healthy dogs (control group); however, ITP of dogs with disk extrusion (group 1) were less than those reported in the experimental study by Kazama et al Based on the observation that SCBF only seems to be influenced where ITP is markedly increased (up to 20/40 mmHg), it may be hypothesized that the effect of a CSF drainage (durotomy) on SCBF may depend on the magnitude of ITP increase.…”
Section: Discussioncontrasting
confidence: 62%
“…Severity of neurologic signs may be associated with higher ITP and could support the hypothesis of SCBF improvement after ITP release. Previous studies with identical set‐up in which paraparetic dogs were enrolled assessed SCBF after durotomy . Blaser et al showed that directly after decompression and durotomy a decrease in SCBF occurred .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study therefore suggest that in dogs undergoing surgical decompression to treat acute thoracolumbar IVDE, a scenario whereby autoregulation of spinal cord blood flow is likely to be compromised and intrathecal pressure increased,22, 48 episodes of hypotension and bradycardia are common. Dogs undergoing longer periods of general anesthesia for more complicated surgical procedures might therefore be subjected to suboptimal spinal cord blood flow, potentially harming SCI recovery 22, 23, 48. As a result, a prospective study design utilizing frequent, direct blood pressure recordings including both extremes of fluctuation in a large number of dogs is required to further evaluate the clinical significance of blood pressure in this population of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Although the oscillometric monitor used in this study1 has previously been evaluated for validity with encouraging results,53 this method does reduce the accuracy of measurements when compared to direct arterial measurement and the results should be considered in light of this. Future studies could therefore better evaluate associations between hemodynamic anesthetic variables and long‐term outcome by utilizing more consistent techniques for prospectively monitoring intraoperative systemic perfusion parameters, such as continuously recorded direct arterial blood pressure recordings,26 as well as defined anesthetic medication protocols and using recently described methods for directly monitoring local indicators of tissue perfusion such as spinal cord blood flow and intraspinal pressure 19, 22, 23, 48. A prospective design in future studies could also utilize recordings of other downstream indicators of tissue perfusion such as plasma l ‐lactate concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation